2018
DOI: 10.1111/1540-6229.12230
|View full text |Cite
|
Sign up to set email alerts
|

Housing Price Dynamics, Mortgage Credit and Reverse Mortgage Demand: Theory and Empirical Evidence

Abstract: This article presents some theoretical and empirical approaches for identifying interactions among fundamental economic variables that determine housing prices. Using home equity conversion mortgage (HECM) loan‐level data, this study quantifies the major risks of reverse mortgages and shows that higher housing prices induce higher demand for reverse mortgages among elderly homeowners. Senior citizens rationally hold pessimistic expectations about future housing price appreciation and lock in their home‐equity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Using data from the US commercial property and mortgage markets over the 1991-2011 period, Arsenault et al (2013) found a positive feedback loop between property prices and mortgage supply. The dynamics between housing prices and reverse mortgage demand were investigated by Chen and Yang (2020), who showed that higher housing prices induced higher demand for reverse mortgages among elderly homeowners.…”
Section: The Relationship Between Bank Credit and Housingmentioning
confidence: 99%
“…Using data from the US commercial property and mortgage markets over the 1991-2011 period, Arsenault et al (2013) found a positive feedback loop between property prices and mortgage supply. The dynamics between housing prices and reverse mortgage demand were investigated by Chen and Yang (2020), who showed that higher housing prices induced higher demand for reverse mortgages among elderly homeowners.…”
Section: The Relationship Between Bank Credit and Housingmentioning
confidence: 99%
“…Hence, reverse mortgages have been an important financial tool for cash-poor seniors to release home equity (Shi and Lee, 2021). Evidence in the pieces work of pieces of literature has documented evidence of underdeveloped reverse mortgage markets in several countries, particularly in Australia, Italy, Netherland, Singapore and the US (Davidoff et al, 2017;Dillingh et al, 2017;Jefferson et al, 2017;Fornero et al, 2016;Phang, 2015) due to several reasons such as poor product growth and high transaction costs (Mitchell and Piggott, 2004), precautionary saving patterns (Nakajima and Telyukova, 2017) and fluctuate house prices (Chen and Yang, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have documented underdeveloped reverse mortgage markets in Australia, Italy, The Netherlands, Singapore and the United States of America (USA) (Phang, 2015;Fornero et al, 2016;Davidoff et al, 2017;Dillingh et al, 2017;Jefferson et al, 2017). Several reasons have been offered for the product's slow growth, including high transaction costs (Mitchell and Piggott, 2004), precautionary savings needs (Nakajima and Telyukova, 2017) and volatile house prices (Chen and Yang, 2020). Consumer preferences also play a role since some older adults perceive housing equity as a financial buffer against adversity, and so they are reluctant to exploit this asset unless in crisis (Morgan et al, 1996;Leviton, 2002).…”
Section: Introductionmentioning
confidence: 99%